On the taxonomic position of ‘Siccia’ yvonneae Kühne, 2007 (Lepidoptera: Nolidae: Nolinae) - László, Gyula M.; Volynkin, Anton V. (Zootaxa, 2019)
Siccia yvonneae Kühne, 2007 described as member of Lithosiini (Erebidae, Arctiinae) is transferred in the present paper to the genus Meganola Dyar, 1898 of Nolini (Nolidae, Nolinae): Meganola yvonneae (Kühne, 2007), comb. nov. Meganola yvonneae is compared to M. conspicua Dyar, 1898 type species of the genus, to M. albula ([Denis & Schiffermüller], 1775) a widespread Palaearctic species and to Manoba lithosiformis László, Ronkay & Ronkay, 2014 described from the Philippines as an example of a Nolinae reminding of the general habitus of Siccia from SE Asia. The adult and genitalia of the Lithosiini Siccia caffra Walker, 1854 are also figured for comparative purposes.